A molecular explanation of wheat starch physicochemical properties related to noodle eating quality. (November 2020) - Li, Qingqing; Li, Cheng; Li, Enpeng; Gilbert, Robert G.; Xu, Bin
Abstract: The relationship between wheat-starch molecular structures (obtained by size-exclusion chromatography), physicochemical properties (swelling power (SP), pasting and thermal properties) and noodle eating qualities were examined. SP was negatively correlated with amylose content and positively correlated with the amounts of amylose long chains and short amylopectin chains. Peak viscosity (PV) was negatively correlated with amylose content and the amount of long amylopectin chains, but positively correlated with the lengths of long amylopectin chains and the amount of short amylopectin chains. Noodles adhesiveness was negatively correlated with the amount of short amylose chains, short amylopectin chains, PV and final viscosity (FV). Noodles hardness was positively correlated with amylose content and long amylopectin chains, but negatively correlated with short amylopectin chains, SP, PV, and FV. All these observations are explained in terms of molecular mechanisms. This provides the first associations between starch molecular fine structures (instead of only amylose content) responsible for starch properties of importance in making noodles. Graphical abstract: Image 1 Highlights: A high proportion of short amylopectin chains increases dough viscoelasticity. A high proportion of short amylose chains increases cookie thickness. A high proportion of short amylose chains decreases the cookie spread ratio.